Harmony in The Frame of Local Wisdom “One Furnace-Three Stones” in Education - M. Zuhri Abu Nawas; Umar Sulaiman; Darnanengsih Darnanengsih; Rusyaid Rusyaid (Dinamika Ilmu, 2022)
This study aims to provide an understanding of the dynamics of the life of the people of Sorong, West Papua related to the harmony of education in family and community life. Harmony, in this case, is related to the mixing of religions in one household, framed in the philosophy of local wisdom called “One Furnace-Three Stones”. This study uses a phenomenological qualitative design. Data were collected through field notes, interviews, and documentation techniques. Data analysis was carried out using the Miles, Huberman, and Saldana techniques: data condensation, data display, and verification/conclusion drawing, as well as data validity using data triangulation techniques. The results showed that the practice of one furnace-three stone became the local wisdom of the people of Sorong, West Papua, namely understanding each other's beliefs about the religion they embraced without having to intervene in the beliefs of other families. The local wisdom creates harmony in education because it focuses on the educational aspect of self. If the education is good for the local community, then all will provide support from the family, youth leaders, and traditional leaders. Internal and external factors cause the supporting factors in realizing harmony in education. Meanwhile, the inhibiting factor in realizing the harmony in education is the low economic background, which narrows the opportunity for children to choose the education they want.